Artificial intelligence in public management: regulatory advances and challenges for its ethical implementation - Gutiérrez Ayala, Jael Rossmery (2026)
This article analyzes the Peruvian legal framework governing the use of artificial intelligence (AI) in public administration, focusing on Law No. 31814 and its Implementing Regulation, with the aim of assessing their scope, limitations, and challenges for ethical and responsible implementation. The study is based on the premise that AI has become a key tool for state modernization, while simultaneously posing significant risks to fundamental rights, administrative transparency, and accountability. The research adopts a qualitative, descriptive-analytical, and comparative approach. It examines national legal norms, documents issued by international organizations—such as UNESCO, the OECD, and the Inter-American Development Bank—and selected institutional experiences within Peruvian public entities. In addition, a comparative analysis with regulatory frameworks from Spain, Chile, and Brazil is conducted to contextualize Peru’s position in the field of algorithmic governance. The findings indicate that although Peru has established an initial regulatory framework aligned with international standards, significant gaps remain in risk assessment, algorithmic auditing, active transparency, and institutional capacity. The article concludes that the effectiveness of Law No. 31814 will largely depend on the adoption of technical guidelines, the strengthening of public sector capacities, and the implementation of effective mechanisms for oversight and citizen participation.